Effectiveness of Liquid Organic Fertilizer Byproduct of Black Soldier Fly Maggot to the Growth of Mustard Plant (Brassica juncea L.) - Laras Nur Janah; Anisa Azmi Nurrisky Apriliani; Afifah Nur Hidayah; Vania Adhelia; Sukirno Sukirno; Budi Setiadi Daryono (Universitas Gadjah Mada, 2023)
The need for consumption of mustard plant (Brassica juncea L.) has increased every year. One of the efforts to increase its production and quality by applications of inorganic and organic fertilizer. This study aimed to evaluate the productivity of mustard plants treated with liquid organic fertilizer, a by-product of black soldier fly (BSF), and inorganic fertilizer (NPK). Mustard plants were grown at Karanggayam Research Station, Caturtunggal, Depok, Sleman, Yogyakarta were treated with water as a control, NPK fertilizer, DoctoRS organic fertilizer at 0.05%, organic fertilizer A, and B at 0.1, 0.15, 0.20, and 0.25%. The effects of treatments to the phenotypic and the chlorophyll of the mustards were done after 2 weeks of treatments. The results showed that there were significant different on the stem height, number of leaves, leaf width, leaf length, and wet weight. These were in line with the total chlorophyll. Liquid organic fertilizer content analysis showed that DoctoRS liquid organic fertilizer and liquid organic fertilizer A were the most in accordance with the national standards for organic fertilizers on the parameters of pH, Mg, Ca, and TPC.